2022
DOI: 10.1097/tp.0000000000004326
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic Regional Perfusion in Pediatric Controlled Donation After Circulatory Death Can Lead to Optimal Organ Utilization and Posttransplant Outcomes

Abstract: Background. The benefits of normothermic regional perfusion (NRP) in posttransplant outcomes after controlled donation after the determination of death by circulatory criteria (cDCD) has been shown in different international adult experiences. However, there is no information on the use of NRP in pediatric cDCD donors. Methods. This is a multicenter, retrospective, observational cohort study describing the pediatric (<18 y) cDCD procedures performed in Spain, using either abdominal NRP or thoracoabdominal NRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Benefits are related to intra-operative assessment of the graft and NRP capacity to regenerate the ischaemic tissue, diminishing post-transplant complications ( 19 ). Miñambres et al ( 1 ), achieved 85% of utilized p-DCD liver grafts obtained with P-NRP (without ex-situ perfusion) and 100% of recovered kidney grafts from p- DCD compared to 0.5% of utilized p-DCD liver grafts obtained with RR ( 20 ).…”
Section: Normothermic Regional Perfusion (Nrp)mentioning
confidence: 99%
See 2 more Smart Citations
“…Benefits are related to intra-operative assessment of the graft and NRP capacity to regenerate the ischaemic tissue, diminishing post-transplant complications ( 19 ). Miñambres et al ( 1 ), achieved 85% of utilized p-DCD liver grafts obtained with P-NRP (without ex-situ perfusion) and 100% of recovered kidney grafts from p- DCD compared to 0.5% of utilized p-DCD liver grafts obtained with RR ( 20 ).…”
Section: Normothermic Regional Perfusion (Nrp)mentioning
confidence: 99%
“…What does the success of NRP in pDCD child donors in Spain ( 1 , 2 ), the first paediatric NRP reported, mean for other countries? In children, given the variability in the DCD-donor from term infant of a few kilograms to adult-sized teenagers, and the greater cerebral blood flow relative to cardiac output in smaller children ( 24 ), it might be argued that greater technical expertise is required to reliably isolate the cerebral circulation, especially in infants.…”
Section: Normothermic Regional Perfusion (Nrp)mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Pediatric NRP cases should be given special consideration with respect to flow rates, cannula size, and surgeon training. 20,21 Recommendation:…”
Section: Beginning Nrp and Honor The Donor And Donor's Family Wishes ...mentioning
confidence: 99%
“…21,22 Compared with conventional organ procurement, the use of abdominal normothermic perfusion (A-NRP) during organ procurement facilitates abdominal organ extraction and improves outcomes in liver and kidney recipients. [23][24][25][26][27][28][29] Although lung donation with A-NRP was described in 2014, 30 a limited number of cases have been reported in the literature. 31 Our group recently reported the largest series published to date and found that LT recipients from DCD donors with simultaneous A-NRP had similar outcomes to those from standard DBD donors in terms of chronic lung allograft dysfunction (CLAD) and survival.…”
Section: Introductionmentioning
confidence: 99%